Effect of the High Hydrostatic Pressure Process on the Microbial and Physicochemical Quality of Shalgam - Ozturk, Eylul; Alpas, Hami; Arici, Muhammet (AMER CHEMICAL SOC, 2024)
The processing of shalgam requires the use of an appropriate processing technique due to yeast overgrowth. With advancements in processing technology, high hydrostatic pressure (HHP) as nonthermal and nonchemical preservation has gained attention for its potential. Response surface methodology with the Box-Behnken experimental design was used to make sense of the effects of HHP parameters, namely, pressure (100-500 MPa), temperature (20-40 degrees C), and time (5-15 min), on microbial and physicochemical factors (pH, total soluble solids, titratable acidity, bioactive compounds, color values). The reduction in the counts of total mesophilic aerobic bacteria, lactic acid bacteria, and yeast-mold increased proportionally with the increase of all pressure levels, application temperatures, and pressurization times (p < 0.05). Stability was maintained in pH, total solubility, and some color parameters such as L*, a*, Delta E, yellow color tone, and red color tone. All findings of the bioactive components (phenolic content, flavonoid content, antioxidant activity, and monomeric anthocyanin content) in the RSM design showed a significant change only in proportion to the square of time (p < 0.05). The optimum pressurization parameter combination of shalgam was determined as a pressure of 367 MPa, temperature of 31.9 degrees C, and process time of 10.5 min. Under these conditions, values of yeast and mold (Y&M) reduction, total flavonoid content (TFC), total monomeric anthocyanin contents (TMACs), titratable acidity (TA), and reducing sugar content (RSC) were obtained as 4.30 log cfu/mL, 192.89 mg QE/100 mL, 11.88 mg/100 mL, 2.41 g(lactic acid)/L, and 6.78 mg/100 mL, respectively. In particular, the findings in the basic color parameters proved that there was no significant change in the saturated red color of the shalgam. Gallic acid, caffeic acid, chlorogenic acid, catechin, cyanidin-3-O-glucoside, malvidin-3-O-glucoside, and peonidin-3-O-glucoside derivatives are dominant phenolic and anthocyanin compounds, which are frequently found in turnip plants. No important losses in bioactive components were observed, despite changes in pressure and temperature parameters. The HHP method can be suggested to have great potential in the processing of shalgam (fermented turnip beverage) in terms of its ability to maintain the flavors, colors, and nutrients, in addition to ensuring microbiological safety when compared to other preservation methods.
Keywords: VAR. ATRORUBENS ALEF.; HIGH-TEMPERATURE; ANTIOXIDANT CAPACITY; POMEGRANATE JUICE; PARAMETERS; PASTEURIZATION; INACTIVATION; ANTHOCYANIN; EXTRACTION; STORAGE; Chemistry